Designing Visually-Enriched Arabic Vocabulary Instruction Using Canva: Empirical Evidence from a Pre-Experimental Study in an Indonesian Islamic Secondary School - Fahriza Ramadhan; Fatma Yulia (IAIN Madura, 2025)
This study aims to examine the effect of Canva-based representative visual media on improving Arabic vocabulary mastery among seventh-grade students at MTs Negeri 2 Medan. Initial classroom observations indicated low vocabulary retention and diminished student motivation, largely due to monotonous instructional methods and limited use of visual learning media. To address these challenges, Canva-based visual media were implemented as an instructional intervention. The study employed a quantitative approach using a pre-experimental design (one-group pretest-posttest). Data analysis involved both descriptive and inferential statistics, specifically utilizing the paired sample t-test with the aid of SPSS. The findings revealed a significant increase in the mean score from 45.42 (pretest) to 81.03 (posttest), with a gain of 35.61 points. A significance value of 0.001 < 0.05 confirmed that the use of Canva-based visual media had a statistically significant impact on students’ Arabic vocabulary acquisition. These findings imply that the integration of digital visual media should be seriously considered in the design of Arabic language instruction at the secondary school level.